Dispersion of carbon nanostructures using PmPV/DCE solution. - Lim, Saw Sean. (2009)
Carbon nanostructures such as carbon nanotubes (CNTs) and graphene exhibit outstanding mechanical and electrical properties, which provide potential use in varieties of advanced applications in nanotechnology and electronic nanodevices. However such application applications are hinder by the poor solubility of carbon nanostructures in aqueous solution due to the nature of strong van der waals interactions between the carbon atoms, which cause them to aggregation and alter their optical-electronic.